Urgensi Iman Kepada Allah dalam Membentuk Akidah Akhlak Peserta Didik di Era Disrupsi - Muamalah Attaqwa; Lutfi Nofianto; Mohammad Syaifuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The era of disruption marked by the rapid development of technology and information brings serious challenges to the world of education, especially in shaping the faith and morals of students. Islamic Religious Education (PAI) has a strategic role in protecting students from the negative influences of this era, through strengthening faith in Allah SWT as the main foundation for character formation. This study aims to analyze the urgency of faith in shaping the faith and morals of students in the midst of the flow of disruption. The approach used is qualitative with a literature study method, reviewing various scientific literature, journals, and relevant documents. The results of the study show that strong faith is the main driver in the commendable behavior of students and a shield against moral relativism and social deviation. Religious education must be integrated comprehensively into the curriculum, teacher training, and learning environments that support the internalization of divine values. In conclusion, strengthening faith in Allah is very urgent as a basis for forming strong faith and morals in facing the challenges of the era of disruption.